Tornado climatology of China. (1st December 2017) - Chen, Jiayi; Cai, Xuhui; Wang, Hongyu; Kang, Ling; Zhang, Hongshen; Song, Yu; Zhu, Hao; Zheng, Wei; Li, Fengju
ABSTRACT: A tornado climatology in China was derived based on a recently completed data set with details on 4763 tornadoes in the period 1948–2012. The tornadoes were rated on the Fujita scale, and design basis tornado wind speeds were estimated. Annual tornadoes were estimated 108 (±44) in China, among which 0–4 exceed F3 on the Fujita scale. Three strongest tornadoes in the data set were rated F4. Assessing from frequency distribution of ratings, tornadoes in China could be mostly of the non‐supercell type. In average of all the country, most tornadoes occur in summer (June–August, about 64%). The peak month is July (31%). Geographically, the majority of tornadoes is distributed in eastern China, with the most frequent tornado occurrence being in the coastal provinces. There are southern type and northern type of tornado occurrence in eastern China. The former peaks in spring, while the latter peaks in summer. Two belts of design basis tornado wind speeds higher than 70 m s −1 were identified (on probability of 10 −7 per year). One extends approximately along the coastline of China from south to north, while the other crosses this belt from east to west, approximately upstream of the Yangtze River. The Yangtze River Delta and Pearl River Delta have design basis tornado wind speeds higher than 90 m s −1, with maxima of 105 and 95 m s −1, respectively. However, by transferring into the enhanced Fujita scale, the wind speed is much lower, with the corresponding maxima being 82 and 76 m s −1 respectively. Abstract : Geographical distribution of more than 4000 tornadoes occurred in China during the period of 1948–2012 is shown in the figure. Collected from multi‐sources, the data are compiled and rated on the Fujita scale. Annual tornadoes in China are estimated as 108 (±44), among which 0–4 exceed F3 Fujita scale. Design basis tornado wind speeds for siting of nuclear power plants in eastern China are calculated with wind speeds in the Fujita scale and converted into the enhanced Fujita scale.